12-month results from the real-life observational treat-to-target and tight-control therapy NOR-Gout study: achievements of the urate target levels and predictors of obtaining this target. Issue 1 (29th March 2021) - Uhlig, Till; Karoliussen, Lars F; Sexton, Joseph; Borgen, Tove; Haavardsholm, Espen A; Kvien, Tore K; Hammer, Hilde Berner
Abstract : Objectives: Gout is often not adequately treated, and we aimed to apply urate lowering treatment (ULT) combined with individual information to achieve target serum urate (sUA) in clinical practice, and to identify predictors of achievement of this sUA target. Methods: Patients with a recent gout flare and sUA >360 µmol/L (>6 mg/dL) were consecutively included in a single-centre study and managed with a treat-to-target approach combining nurse-led information about gout with ULT. All patients were assessed with tight controls at baseline, 1, 2, 3, 6, 9 and 12 months including clinical examination, information on demographics, lifestyle, self-efficacy and beliefs about medicines. The treatment target was sUA <360 µmol/L and multivariable logistic regression was used to identify predictors of target attainment with ORs and 95% CIs. Results: Of 211 patients (mean age 56.4 years, disease duration 7.8 years, 95% males), 186 completed the 12-month study. Mean sUA levels decreased from baseline mean 500 to 311 µmol/L at 12 months with 85.5% achieving the treatment target. Alcohol consumption at least weekly versus less frequently (OR 0.14; 95% CI 0.04 to 0.55) as well as beliefs in overuse of medicines (OR per unit 0.77; 95 CI 0.62 to 0.94) decreased the chance of reaching the treatment target, while higher self-efficacy for arthritis symptoms (OR 1.49 per 10 units; 95% CI 1.09 to 2.05) increased the likelihood. Conclusions: This study shows that target sUA can be achieved with ULT in most patients. Less self-reported alcohol consumption, low beliefs in overuse of medicines and higher self-efficacy are associated with treatment success.